Новые виды клещей рода Bonomoia Oudemans, 1911 (Anoetidae, Sarcoptiformes) - Севастьянов, В.Д. (Вестник зоологии, 1973)
In the suburbs of Odessa the males, females and hypopus of Bonomoia piicturata sp. 11. under bark of Populus nigra L.. in the Ichmelnitsky region the males and females of B. probata sp. 11. under the bark of Populus tremula L. were found. In the forests of Mariiskaya ASSR B. recondita sp. n. inhabits ant-hills of Myrmica ruginoidis N y 1.